Batman and Superman. Battle of the super sons [videorecording (Blu-Ray)] - Adams, Jeremy (Screenwriter) (Warner Bros. Entertainment, 2022)
When eleven-year-old Jonathan Kent discovers he has superpowers, the half-Kryptonian is thrust into the world of heroes and villains now under attack by a malevolent alien force known as Starro! Joined by assassin-turned Boy Wonder, Damian Wayne, Jonathan must race against time to save their fathers (Superman and Batman) and the world by becoming the Super-sons they were destined to be!